Benefits versus Costs of Price Supports - Howell, L. D. (Quarterly Journal of Economics, 1954)
Introduction, 115. — I. Economic benefits and costs, 116; short-time results, 116; longer-time results, 123. — II. Feasibility of financing and operating the programs, 127. — III. Summary and conclusions, 128.